Deodorizing and formaldehyde-removing dispersion liquid and preparation method thereof

Through multi -compulsory technology, combined with micro -porous materials, titanium dioxide, nano -clustered copper particles and metal matched materials, the existing existing taste of formaldehyde removal materials cannot be stable for a long time under the action of light thermal action, realizing high stability and functions Differential formaldehyde dispersion liquid.

CN119327260AActive Publication Date: 2025-01-21SHANGHAI HUZHENG IND CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411873114.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-01-21
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing odor removal and formaldehyde removal materials cannot be stable for a long time under the action of photothermal heat, and organic and inorganic composite materials have challenges in stability, making it difficult to achieve outstanding functional effects.

Method used

Through multiple composite technology, combining micro-nano porous materials, titanium dioxide, nanocluster copper particles and metal complexes, the deodorization and formaldehyde removal functions of physical adsorption and chemical decomposition are achieved.

Benefits of technology

It significantly improves the stability and functional effects of removing formaldehyde deductive liquids, achieves better flavor removal effects and long -term stability, and plays outstanding functions in coating, spray and other products.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses odor and formaldehyde removal dispersion liquid and a preparation method thereof, and belongs to the technical field of environment-friendly products. The odor and formaldehyde removal dispersion liquid comprises the following components: 5-10 wt% of porous active particles; 0.01 wt% to 0.02 wt% of nano cluster copper; 1 to 3 wt% of an antibacterial metal complex; 3-5 wt% of an organic solvent; 0.1 to 0.3 wt% of a dispersant; a surfactant: 0.05 to 0.1 wt%; and the balance of water. Through multiple compounding of a micro-nano porous material, titanium dioxide, nanocluster copper particles, a metal complex and the like, odor and formaldehyde removal functions of physical adsorption and chemical decomposition are realized. The prepared odor and formaldehyde removal dispersion liquid can be applied to odor and formaldehyde removal coatings, sprays, finishing agents and other products, and prominent functions are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a deodorizing and formaldehyde removing dispersion liquid and a preparation method thereof, and belongs to the technical field of environmentally friendly products. Background Art

[0002] The concept of environmentally friendly, healthy and safe living has long been deeply rooted in people's hearts. In terms of indoor furniture, decoration and new cars, there are high requirements for deodorization and formaldehyde removal. At the same time, there are also many deodorization requirements for odors in life, such as smoke, kitchen waste, toilet odors, etc. Odors are often accompanied by the metabolism of bacteria and germs, which also brings harm to people's health. There have also been a lot of research and development in deodorization and formaldehyde removal materials.

[0003] Chinese patent CN108434954A discloses a multifunctional formaldehyde removal deodorant, which realizes the functions of antibacterial and formaldehyde removal through cypress essential oil, modified parachloro-metaxylenol, tea tree essential oil, blue cypress essential oil and other effective ingredients such as N-ethyl-N soybean ethyl sulfate marin. Chinese patent CN110743357A discloses a formaldehyde removal liquid containing bio-enzyme additives, which realizes the function through photocatalysts such as nano-titanium dioxide and nano-zinc oxide, bio-enzyme additives, composite resins and auxiliary ingredients. Chinese patent CN110947289A discloses a nano-bactericidal deodorant, which realizes the functions of sustained-release sterilization and formaldehyde removal through modified zeolite adsorption of nano-titanium dioxide and nano-silver. Based on these studies, the current deodorization and formaldehyde removal functions not only focus on functional effectiveness, but also on long-term effectiveness and stability. Plant essential oils, biological enzymes and other organic compound ingredients have good functions in removing odor and formaldehyde, but they are often not stable for a long time under the action of light and heat; inorganic nanomaterials have great advantages in stable function. Organic-inorganic composites are also the current development trend of materials. High-stability organic materials and high-efficiency composite inorganic nanoparticles are expected to achieve outstanding functional effects. Summary of the invention

[0004] According to one aspect of the present application, a deodorizing and formaldehyde removing dispersion is provided, which realizes the deodorizing and formaldehyde removing functions of physical adsorption and chemical decomposition through multiple composites of micro-nano porous materials, titanium dioxide, nano-cluster copper particles, metal complexes, etc. The prepared deodorizing and formaldehyde removing dispersion can be used in deodorizing and formaldehyde removing coatings, sprays, finishing agents and other products to achieve outstanding functions.

[0005] The deodorizing and formaldehyde removing dispersion described in the present application comprises the following components: Porous active particles: 5-10wt%; Nanocluster copper: 0.01-0.02wt%; Antibacterial metal complexes: 1-3wt%; Organic solvent: 3-5wt%; Dispersant: 0.1-0.3wt%; Surfactant: 0.05-0.1wt%; The balance is water.

[0006] Optionally, the porous active particles are zeolite particles loaded with titanium dioxide.

[0007] Optionally, the porous active particles have a particle size of 1-3 μm.

[0008] Optionally, the particle size of the nanocluster copper is 100-200 nm.

[0009] Optionally, the antibacterial metal complex is a chitosan zinc complex and a chitosan copper complex.

[0010] Optionally, the molecular weight of chitosan in the chitosan zinc complex and the chitosan copper complex is 100,000-150,000 g / mol, and the degree of deacetylation is 80-85%.

[0011] Optionally, the dispersant is polyvinyl pyrrolidone.

[0012] Optionally, the surfactant is sorbitan fatty acid ester.

[0013] Optionally, the organic solvent is isopropanol.

[0014] Optionally, the surfactant is sorbitan fatty acid ester.

[0015] Optionally, the method for preparing the porous active particles comprises the following steps: (1) Mix anhydrous ethanol, hydrochloric acid and deionized water to obtain solution A; (2) mixing zeolite particles, anhydrous ethanol and butyl titanate to obtain solution B; (3) Mix solution A and solution B; (4) Filter, wash, vacuum dry and calcine.

[0016] Optionally, in step (1), the volume ratio of anhydrous ethanol, hydrochloric acid and deionized water is (200-300):(2-4):(5-8).

[0017] Optionally, in step (2), the addition ratio of zeolite particles, anhydrous ethanol and butyl titanate is (5-10) g: (255-380) mL: (15-20) g.

[0018] Optionally, the volume ratio of hydrochloric acid in step (1) to anhydrous ethanol in step (2) is (2-4): (255-380).

[0019] Optionally, step (3) comprises: adding solution A into solution B at a rate of 5-10 ml / min.

[0020] Optionally, in step (4), the calcination temperature is 400-500° C. and the calcination time is 4-6 hours.

[0021] Optionally, in step (4), the vacuum drying temperature is 60-80°C.

[0022] Optionally, the method for preparing the porous active particles comprises the following steps: (1) According to the volume ratio, 200-300 parts of anhydrous ethanol, 2-4 parts of hydrochloric acid and 5-8 parts of deionized water are thoroughly mixed to obtain solution A.

[0023] (2) 5-10 parts by weight of zeolite particles are soaked in 200-300 parts by volume of anhydrous ethanol and ultrasonicated, and the mixture is allowed to stand for 24 hours. 15-20 parts by weight of butyl titanate is dissolved in 55-80 parts by volume of anhydrous ethanol and then added thereto, and the mixture is ultrasonicated for 10-30 minutes to form a solution B. (3) Add solution A to solution B at 5-10 ml / min and stir at 40-50°C for 1-3 h.

[0024] (4) Filter and wash, vacuum dry at 60-80℃, and calcine at 400-500℃ for 4-6h.

[0025] Optionally, the method for preparing the antibacterial metal complex comprises the following steps: (I) mixing chitosan, weak acid, organic zinc salt and organic copper salt to obtain a mixture 1; (II) mixing mixture 1 and a nonionic surfactant, and adjusting the pH to 6.5-7.5 to obtain mixture 2; (III) Mix the mixture 2 and the glutaraldehyde aqueous solution, centrifuge, wash and vacuum dry.

[0026] Optionally, the mass ratio of chitosan, weak acid, organic zinc salt and organic copper salt is (1-3): (150-400): (3.5-8.4): (1.9-4.8).

[0027] Optionally, the molecular weight of the chitosan is 100,000-150,000 g / mol, and the degree of deacetylation is 80-85%.

[0028] Optionally, the mass ratio of the nonionic surfactant to chitosan is (0.01-0.03):(1-3).

[0029] Optionally, the weak acid is acetic acid.

[0030] Optionally, the organic zinc salt is zinc acetate.

[0031] Optionally, the organic copper salt is copper acetate.

[0032] Optionally, the nonionic surfactant is sorbitan fatty acid ester.

[0033] Optionally, the concentration of the glutaraldehyde aqueous solution is 20-30wt%; preferably, the concentration of the glutaraldehyde aqueous solution is 25wt%.

[0034] Optionally, the mass ratio of the glutaraldehyde aqueous solution to chitosan is (0.5-1):(1-3).

[0035] Optionally, in the method for preparing the antibacterial metal complex, the step (III) comprises: adding glutaraldehyde aqueous solution dropwise to the mixture 2, wherein the dropwise adding method is to add 1 drop of glutaraldehyde aqueous solution every 20-30 seconds.

[0036] Optionally, the method for preparing the antibacterial metal complex comprises the following steps: (I) Dissolve 1-3 parts of chitosan in 150-400 parts of acetic acid according to the mass ratio, add 3.5-8.4 parts of zinc acetate and 1.9-4.8 parts of copper acetate to the solution, and stir for 0.5-1h.

[0037] (II) Add 0.01-0.03 parts of sorbitan fatty acid ester and aqueous ammonia until the pH is 6.5-7.5, stir and reflux at 70-75°C for 5-8 hours, and then cool to room temperature.

[0038] (III) Add 0.5-1 part of 25 wt% glutaraldehyde aqueous solution dropwise, stir for 1-3 hours, centrifuge and wash, and dry in vacuum at 60-80°C.

[0039] On the other hand, the present application provides a method for preparing the deodorizing and formaldehyde-removing dispersion, which comprises: mixing porous active particles, nanocluster copper, antibacterial metal complexes, organic solvents, dispersants, surfactants, and water to obtain the dispersion.

[0040] Optionally, the method for preparing the deodorizing and formaldehyde removing dispersion comprises the following steps: (a) The porous active particles and the copper nanoclusters are mixed with solution 1 to obtain solution a; (b) mixing the antibacterial metal complex, sorbitan fatty acid ester and the remainder of water to obtain a solution b; (c) Solution a and solution b are mixed and sieved.

[0041] Optionally, in step (c), the product is sieved through a 200-mesh sieve.

[0042] Optionally, the solution 1 comprises a dispersant, an organic solvent and water I, and the mass ratio of the organic solvent to water I is 1:(9-11); preferably, the mass ratio of the organic solvent to water I is 1:10.

[0043] The deodorizing and formaldehyde-removing dispersion described in the present application can be used in deodorizing and formaldehyde-removing coatings, sprays, finishing agents and other products to achieve outstanding functions.

[0044] The beneficial effects of this application include: (1) The inventors found in the study of deodorizing and formaldehyde removing dispersion that the dispersion was unstable, which in turn affected its deodorizing and formaldehyde removing properties. The inventors still failed to effectively solve the stability of the dispersion by simply changing the types of dispersants and surfactants, and the deodorizing and formaldehyde removing properties were still not improved. In subsequent studies, the inventors found that controlling the particle size of zeolite, the molecular weight and deacetylation degree of chitosan, and the reaction of porous active particles and antibacterial metal complexes solved the problem of the instability of the dispersion and significantly improved the deodorizing and formaldehyde removing properties. The possible reason is that controlling the particle size of zeolite and the reaction of porous active particles can regulate the size of titanium dioxide particles and the crystal distribution after subsequent calcination; controlling the molecular weight and deacetylation degree of chitosan, as well as the reaction of antibacterial metal complexes, makes the coordination of chitosan and metal ions in an appropriate state, and the chitosan with a cross-linked network structure obtained can exist uniformly and stably in the solution with porous active particles and nanocluster copper, thereby improving the deodorizing and formaldehyde removing properties and solving the problem that organic particles and inorganic particles cannot be balanced and stable.

[0045] (2) The deodorizing and formaldehyde-removing dispersion prepared in the present application is compounded with multiple functional materials such as porous active particles, nanocluster copper particles, and metal complex particles to achieve the functions of deodorizing and removing formaldehyde. On the one hand, the high porosity of porous active particles, nanocluster copper particles, etc. enhances the effective physical adsorption of odor molecules. On the other hand, the catalytic decomposition of formaldehyde and other components by titanium dioxide nanoparticles, as well as the active antibacterial effects of nano-copper and chitosan zinc / copper, fundamentally eliminate the source of odor. In addition, a composite synergistic effect is formed between the materials, and the entire system maintains good stability. Compared with general deodorizing and formaldehyde-removing materials, the deodorizing and formaldehyde-removing dispersion prepared in the present application has better deodorizing effect and long-term stability, and can play an outstanding deodorizing and formaldehyde-removing function in deodorizing products such as coatings and sprays. DETAILED DESCRIPTION

[0046] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0047] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0048] The nanocluster copper is nano-copper powder CU-P100 produced by Shanghai Huzheng Industrial Co., Ltd.

[0049] Example 1: Porous active particles were prepared by the following method: (1) 1500 ml of ethanol, 15 ml of hydrochloric acid and 40 ml of water are thoroughly mixed to form solution A.

[0050] (2) 40 g of zeolite (particle size 2 μm) was soaked in 1500 ml of ethanol and ultrasonicated. The mixture was allowed to stand for 24 h. 75 g of butyl titanate was dissolved in 350 ml of ethanol and added to the mixture. The mixture was ultrasonicated for 30 min to form solution B.

[0051] (3) Solution A was added to solution B at a rate of 5 ml / min and stirred at 50°C for 2 h.

[0052] (4) Filter and wash, vacuum dry at 70°C, and calcine at 400°C for 6 h.

[0053] The antimicrobial metal complexes were prepared by the following method: (1) Dissolve 7.5 g of chitosan (molecular weight 100,000 g / mol, degree of deacetylation 85%) in 750 g of acetic acid, add 23 g of zinc acetate and 13 g of copper acetate, and stir for 1 h.

[0054] (2) Add 0.05 g of dehydrated sorbitan fatty acid ester and ammonia water until the pH reaches 6.5. Stir and reflux at 70°C for 8 h, then cool to room temperature.

[0055] (3) Add 2.5 g of 25 wt% glutaraldehyde aqueous solution at a rate of 20 s per drop, stir for 3 h, centrifuge and wash, and dry in a vacuum at 70 °C.

[0056] The components were weighed, and 40 g of porous active particles and 0.05 g of nanocluster copper were mixed and dispersed in a mixed solution of 275 g of 0.18 wt% polyvinyl pyrrolidone in isopropanol and water (the mass ratio of isopropanol to water was 1:10); 7.5 g of the antibacterial metal complex was dispersed in 176.7 g of 0.14 wt% aqueous solution of dehydrated sorbitan fatty acid ester; the two dispersions were stirred at high speed and ultrasonicated for 3 h respectively, the solutions were mixed and stirred for 4 h, and passed through a 200-mesh sieve to obtain a deodorizing and formaldehyde-removing dispersion.

[0057] Example 2: Porous active particles were prepared by the following method: (1) 1500 ml of ethanol, 15 ml of hydrochloric acid and 40 ml of water are thoroughly mixed to form solution A.

[0058] (2) 40 g of zeolite (particle size 2 μm) was soaked in 1400 ml of ethanol and ultrasonicated. The mixture was allowed to stand for 24 h. 85 g of butyl titanate was dissolved in 350 ml of ethanol and added thereto. The mixture was ultrasonicated for 30 min to form solution B.

[0059] (3) Solution A was added to solution B at a rate of 8 ml / min and stirred at 50 °C for 3 h.

[0060] (4) Filter and wash, vacuum dry at 70°C, and calcine at 500°C for 4 h.

[0061] The antimicrobial metal complexes were prepared by the following method: (1) Dissolve 10 g of chitosan (molecular weight 100,000 g / mol, degree of deacetylation 85%) in 1150 g of acetic acid, add 19.5 g of zinc acetate and 14.5 g of copper acetate, and stir for 1 h.

[0062] (2) Add 0.05 g of dehydrated sorbitan fatty acid ester and aqueous ammonia until the pH reaches 6.5. Stir and reflux at 70°C for 6 h, then cool to room temperature.

[0063] (3) Add 3 g of 25 wt% glutaraldehyde aqueous solution at a rate of 30 s per drop, stir for 3 h, centrifuge and wash, and dry in a vacuum at 70 °C.

[0064] The components were weighed, and 40 g of the porous active particles and 0.1 g of the nanocluster copper were dispersed in a mixed solution of 275 g of 0.18 wt% polyvinyl pyrrolidone in isopropanol and water (the mass ratio of isopropanol to water was 1:10); 10 g of the antibacterial metal complex was dispersed in 174.15 g of 0.14 wt% aqueous solution of sorbitan fatty acid ester; the two dispersions were stirred at high speed and ultrasonicated for 3 h respectively, the solutions were mixed and stirred for 5 h, and passed through a 200-mesh sieve to obtain a deodorizing and formaldehyde-removing dispersion.

[0065] Example 3: Porous active particles were prepared by the following method: (1) 1500 ml of ethanol, 15 ml of hydrochloric acid and 40 ml of water are thoroughly mixed to form solution A.

[0066] (2) 50 g of zeolite (particle size 2 μm) was soaked in 1500 ml of ethanol and ultrasonicated. The mixture was allowed to stand for 24 h. 100 g of butyl titanate was dissolved in 350 ml of ethanol and added to the mixture. The mixture was ultrasonicated for 30 min to form solution B.

[0067] (3) Solution A was added to solution B at a rate of 10 ml / min and stirred at 50 °C for 3 h.

[0068] (4) Filter and wash, vacuum dry at 70°C, and calcine at 500°C for 5h.

[0069] The antimicrobial metal complexes were prepared by the following method: (1) Dissolve 7.5 g of chitosan (molecular weight 150,000 g / mol, degree of deacetylation 80%) in 1,000 g of acetic acid, add 28 g of zinc acetate and 16 g of copper acetate, and stir for 1 h.

[0070] (2) Add 0.05 g of dehydrated sorbitan fatty acid ester and aqueous ammonia until the pH reaches 7.0. Stir and reflux at 70°C for 8 h, then cool to room temperature.

[0071] (3) Add 3.5 g of 25 wt% glutaraldehyde aqueous solution at a rate of 30 s per drop, stir for 3 h, centrifuge and wash, and dry in a vacuum at 70 °C.

[0072] The components were weighed, and 50 g of porous active particles and 0.05 g of nanocluster copper were mixed and dispersed in a mixed solution of 275 g of 0.18 wt% polyvinyl pyrrolidone in isopropanol and water (the mass ratio of isopropanol to water was 1:10); 7.5 g of the antibacterial metal complex was dispersed in 166.7 g of 0.15 wt% aqueous solution of dehydrated sorbitan fatty acid ester; the two dispersions were stirred at high speed and ultrasonicated for 3 h respectively, the solutions were mixed and stirred for 5 h, and passed through a 200-mesh sieve to obtain a deodorizing and formaldehyde-removing dispersion.

[0073] Example 4: The preparation of porous active particles is the same as that of Example 3, except that the zeolite particle size is 10 μm.

[0074] The preparation of the antibacterial metal complex and the deodorizing and formaldehyde removing dispersion is the same as that in Example 3.

[0075] Example 5: Preparation of antibacterial metal complexes The same as Example 3, except that the degree of deacetylation of chitosan is 90% and the molecular weight is 200000 g / mol.

[0076] The preparation of porous active particles and deodorizing and formaldehyde removing dispersion is the same as that in Example 3.

[0077] Example 6: Preparation of antibacterial metal complexes The same as Example 3, except that the degree of deacetylation of chitosan is 70% and the molecular weight is 1000000 g / mol.

[0078] The preparation of porous active particles and deodorizing and formaldehyde removing dispersion is the same as that in Example 3.

[0079] Example 7: Preparation of porous active particles The method is the same as Example 3, except that, in the preparation of the porous active particles, step (3) is as follows: solution A is added to solution B at 2 ml / min and stirred at 50° C. for 3 h.

[0080] The preparation of the antibacterial metal complex and the deodorizing and formaldehyde removing dispersion is the same as that in Example 3.

[0081] Example 8: Preparation of porous active particles The method is the same as Example 3, except that, in the preparation of the porous active particles, step (3) is as follows: solution A is added to solution B at 15 ml / min and stirred at 50° C. for 3 h.

[0082] The preparation of the antibacterial metal complex and the deodorizing and formaldehyde removing dispersion is the same as that in Example 3.

[0083] Example 9: Preparation of antibacterial metal complexes The same as Example 3, except that in the preparation of the antibacterial metal complexes, step (3) is: adding 3.5 g of 25 wt% glutaraldehyde aqueous solution at a rate of 10 s per drop, stirring for 3 h, centrifuging and washing, and drying in vacuum at 70°C.

[0084] The preparation of porous active particles and deodorizing and formaldehyde removing dispersion is the same as that in Example 3.

[0085] Example 10: Preparation of antibacterial metal complex The same as Example 3, except that in the preparation of the antibacterial metal complex, step (3) is: adding 3.5 g of 25 wt% glutaraldehyde aqueous solution at a rate of 50 s per drop, stirring for 3 h, centrifuging and washing, and drying in vacuum at 70°C.

[0086] The preparation of porous active particles and deodorizing and formaldehyde removing dispersion is the same as that in Example 3.

[0087] Test Example: The deodorizing and formaldehyde-removing dispersions prepared in each embodiment were subjected to performance tests, including formaldehyde removal test, deodorization (ammonia and hydrogen sulfide) test, and antibacterial test.

[0088] The formaldehyde removal test was conducted according to the standard QB / T2761-2006 "Method for Determining the Purification Effect of Indoor Air Purification Products". The experimental device was arranged. Five layers of medical degreased gauze were rolled on two glass rods and fixed upright in a bottle. 200 ml of 0.2% formaldehyde solution was poured in. The gauze was completely wetted before use and placed in a test chamber with a 1W light source. 100 g of each sample of the embodiment was sprayed on a 1m 2 The base paper was placed in each test chamber, and the formaldehyde concentration difference between the test chamber and the blank chamber was tested 24 hours later. The formaldehyde removal rate was the ratio of the concentration difference between the test chamber and the blank chamber to the blank concentration.

[0089] The hydrogen sulfide removal rate and ammonia removal rate are tested in accordance with the standard CJ / T516-2017 "Technical Requirements for Deodorants for Domestic Waste".

[0090] Determination of hydrogen sulfide removal effect: Under normal temperature (20°C) and normal pressure (1 standard atmosphere), the initial concentration of 0.15 mg / m 315L of hydrogen sulfide gas was passed through large bubble absorption tubes containing 10mL of each example sample at a flow rate of 1L / min. The treated gas was collected and the concentration was determined by methylene blue spectrophotometry according to GB / T 11742-2009.

[0091] Determination of ammonia removal effect: Under normal temperature (20°C) and normal pressure (1 standard atmosphere), the initial concentration of 1.5 mg / m 3 15L of ammonia gas was passed through a large bubble absorption tube containing 10mL of each example sample at a flow rate of 1L / min. The treated gas was collected and the concentration was measured by Nessler's reagent spectrophotometry according to HJ533-2009.

[0092] The antibacterial test was carried out according to the antibacterial performance test method of C4 dissolution antibacterial (inhibitory) product in Appendix C of GB15979-2002 "Hygiene Standard for Disposable Sanitary Products", with an action time of 2 minutes and test bacteria of Staphylococcus aureus and Escherichia coli.

[0093] The test results are shown in Table 1. It can be seen that Examples 1-3 have the functions of formaldehyde removal, odor removal (hydrogen sulfide, ammonia) and antibacterial deodorization, with a formaldehyde removal rate of more than 95%, a hydrogen sulfide removal rate of more than 92%, an ammonia removal rate of more than 96%, and an antibacterial rate of 99.9%. Therefore, the deodorizing and formaldehyde removing dispersion has a good application prospect in the relevant functional application market field.

[0094] Table 1 Formaldehyde removal rate Hydrogen sulfide removal rate Ammonia removal rate Staphylococcus aureus inhibition rate Escherichia coli inhibition rate Example 1 95.10% 92.40% 96.70% 99.90% 99.90% Example 2 96.30% 92.80% 97.60% 99.90% 99.90% Example 3 95.50% 92.50% 97.20% 99.90% 99.90% Example 4 76.32% 70.25% 74.10% 86.14% 84.59% Example 5 84.30% 81.15% 82.64% 83.74% 82.98% Example 6 84.65% 81.54% 82.43% 81.24% 80.76% Example 7 87.62% 84.76% 85.34% 88.97% 86.79% Example 8 82.56% 81.30% 83.61% 89.58% 88.94% Example 9 85.73% 82.94% 86.10% 87.53% 89.90% Example 10 80.20% 76.14% 80.34% 86.50% 83.82% The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A deodorizing and formaldehyde removing dispersion, characterized in that: It includes the following ingredients: porous active particles: 5-10wt%; Nanocluster copper: 0.01-0.02wt%; Antibacterial metal complex: 1-3wt%; Organic solvent: 3-5wt%; Dispersant: 0.1-0.3wt%; Surfactant: 0.05-0.1wt%; the balance is water; The porous active particles are zeolite particles loaded with titanium dioxide; The antibacterial metal complex is a chitosan zinc complex and a chitosan copper complex.

2. The deodorizing and formaldehyde removing dispersion according to claim 1, characterized in that: The particle size of the porous active particles is 1-3 μm.

3. The deodorizing and formaldehyde removing dispersion according to claim 1, characterized in that: The particle size of the nano-cluster copper is 100-200 nm.

4. The deodorizing and formaldehyde removing dispersion according to claim 1, characterized in that: The molecular weight of chitosan in the chitosan zinc complex and the chitosan copper complex is 100000-150000 g / mol, and the deacetylation degree is 80-85%.

5. The deodorizing and formaldehyde removing dispersion according to any one of claims 1 to 4, characterized in that: The method for preparing the porous active particles comprises the following steps: (1) Mix anhydrous ethanol, hydrochloric acid and deionized water to obtain solution A; (2) mixing zeolite particles, anhydrous ethanol and butyl titanate to obtain solution B; (3) Mix solution A and solution B; (4) Filter, wash, vacuum dry and calcine.

6. The deodorizing and formaldehyde removing dispersion according to claim 5, characterized in that: The step (3) comprises: adding solution A into solution B at a rate of 5-10 ml / min.

7. The deodorizing and formaldehyde removing dispersion according to claim 5, characterized in that: In the step (4), the calcination temperature is 400-500° C. and the calcination time is 4-6 hours.

8. The deodorizing and formaldehyde removing dispersion according to any one of claims 1 to 4, characterized in that: The preparation method of the antibacterial metal complex comprises the following steps: (I) mixing chitosan, weak acid, organic zinc salt and organic copper salt to obtain a mixture 1; (II) Mixing mixture 1 and a nonionic surfactant, and adjusting the pH to 6.5-7.5 to obtain mixture 2; (III) Mixture 2 and aqueous glutaraldehyde solution are mixed, centrifuged, washed, and vacuum dried.

9. The deodorizing and formaldehyde removing dispersion according to claim 8, characterized in that: In the method for preparing the antibacterial metal complex, the step (III) comprises: adding glutaraldehyde aqueous solution dropwise to the mixture 2, wherein the dropwise adding method is to add 1 drop of glutaraldehyde aqueous solution every 20-30 seconds.

10. A method for preparing the deodorizing and formaldehyde removing dispersion according to any one of claims 1 to 9, characterized in that: include: The porous active particles, nano-cluster copper, antibacterial metal complex, organic solvent, dispersant, surfactant and water are mixed to obtain the product.

Citation Information

Patent Citations

  • Multifunctional formaldehyde-removing deodorant

    CN108434954A

  • Formaldehyde removal liquid added with biological enzyme aid, and preparation method thereof

    CN110743357A

  • Nano sterilizing and deodorizing agent

    CN110947289A

  • A photocatalyst air cleaning agent and a preparing method thereof

    CN106378199A

  • Formaldehyde removal coating and preparation method thereof

    CN109880465A